2019
DOI: 10.17826/cumj.441022
|View full text |Cite
|
Sign up to set email alerts
|

Üniversite öğrencilerinin evlilik tutumlarını etkileyen faktörler

Abstract: Öz Purpose: This descriptive study aims to identify factors affecting attitudes of university students on marriage. Material and Methods: The sample consists of 791 students. The data were collected with "Personal Information Form" and was prepared by the researchers and "Inonu Marriage Attitude Scale". Results: The ideal marriage age was determined to be 24 years and over for 74.6% of the girls and 25-29 years for 77% of the boys. Of the students, 95.2% stated that they had to decide who to marry, 68.5% said … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…Because 26.7% of the marriage files contained no data regarding the age of the person applying for the marriage permit, we think the actual rate might be higher and the results from our study to be consistent with those in the literature. Studies conducted in Turkey have determined the ideal age of marriage for men to be higher than for women (Akbaş et al, 2019). This situation may be related to men taking on the economic responsibility and anxiety of starting work and thus get married at a later age in order to establish this order.…”
Section: Discussionmentioning
confidence: 99%
“…Because 26.7% of the marriage files contained no data regarding the age of the person applying for the marriage permit, we think the actual rate might be higher and the results from our study to be consistent with those in the literature. Studies conducted in Turkey have determined the ideal age of marriage for men to be higher than for women (Akbaş et al, 2019). This situation may be related to men taking on the economic responsibility and anxiety of starting work and thus get married at a later age in order to establish this order.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7] In a study conducted to determine the factors affecting marriage attitudes; It is reported that students' attitudes towards marriage decided by, the happiness of their parents, their family's views on marriage, their fear of marriage, their families' marriage status, their views on the ideal marriage age for men and women, and their gender. 8 Although the factors affecting the marriage attitude vary, there is no study in the literature examining the effect of fear of birth on marriage attitude. In this direction, it is thought that the fear of birth before pregnancy will affect the attitude towards marriage and that it may be related to the fear of birth and marriage attitude.…”
Section: Introductionmentioning
confidence: 99%
“…Although there has been a decline in the number of marriages in recent years in Turkey (Turkish Statistical Institute (TurkStat), 2020), young people do not fear marriage (Akbaş et al, 2019;Bağ, 2019), and only a small portion of them consider marriage as unnecessary (Ișmen-Gazioğlu, 2006). Köroğlu (2013) determined that the vast majority of young people attach importance to marriage.…”
Section: Introductionmentioning
confidence: 99%